Monitoring and mitigating bioacoustic impacts from seismic surveys: The Australian Perspective - Erbe, Christine (2013)
In Australia, proponents of seismic surveys and other operations emitting underwater noise have to prepare an Environmental Plan (EP) for approval by the regulator before operations can commence. In support of the EP, large amounts of data are often collected, such as baseline data on the marine soundscape, the physical and biological environment, operational noise characteristics etc. More data (on underwater noise, animal abundance and behaviour etc.) is sometimes collected during operations as part of monitoring and mitigation plans. Australia's offshore oil & gas industry has recently come together to share data from bioacoustic environmental impact assessments, yielding charts of baseline soundscape characteristics, catalogues of anthropogenic source characteristics, improved models for sound field prediction, and growing databases of animal behaviour, abundance and migration. This data sharing will ultimately help to streamline the environmental approval process.